2016
DOI: 10.1097/md.0000000000002859
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Rheumatoid Arthritis

Abstract: Although many epidemiological studies have investigated the association between body mass index (BMI) and risk of rheumatoid (RA), the results have been inconsistent. Therefore, we performed a dose-response meta-analysis to quantify the dose-response association between BMI and RA risk.We systematically searched PubMed, Embase, and Web of Science databases and reference lists of articles for relevant studies published before August 2014 using terms related to BMI and RA. Fixed or random-effects models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Obesity is one of the described risk factors for the development of RA and it negatively affects disease activity and treatment outcomes [ 3 , 4 , 7–9 ]. Although it has been shown that bariatric surgery–induced weight loss results in decreased disease activity and improved response to treatment, the effect of bariatric surgery on the incidence of RA is not known [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is one of the described risk factors for the development of RA and it negatively affects disease activity and treatment outcomes [ 3 , 4 , 7–9 ]. Although it has been shown that bariatric surgery–induced weight loss results in decreased disease activity and improved response to treatment, the effect of bariatric surgery on the incidence of RA is not known [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been identified that represent a risk for the development of RA, including female sex, genetic predisposition and smoking [ 2 ]. Large meta-analyses have also shown that obesity is among the risk factors for the development of RA, especially among women [ 3–6 ]. Moreover, in subjects with RA, obesity is associated with higher disease activity and lower chance to achieve sustained remission [ 7–10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wnt5a is markedly upregulated in visceral adipose tissue (VAT) and correlates strongly with indices of inflammation and diabetes mellitus [10, 51]. Despite the existence of “rheumatoid cachexia” in late-stage disease, large scale meta-analysis reveals that obesity is a risk factor for RA that is associated with disease severity [52, 53]. It has been proposed that adipokines, cytokines secreted by adipose tissue, are molecular drivers of both diseases [52, 54].…”
Section: Discussionmentioning
confidence: 99%
“…We dichotomized BMI <25 vs. ≥25 kg/m 2 based on the World Health Organization definition of normal vs. overweight/obese [15], as well as literature supporting this as a clinically important cutoff for RA risk [10, 11, 17, 44, 45]. Subjects were also cross-classified into four groups according to their BMI (<25 vs. ≥25 kg/m 2 ) and ACPA status (<2 vs. ≥2 subtypes).…”
Section: Methodsmentioning
confidence: 99%
“…Recent meta-analyses of BMI’s effect on RA risk reported that BMI ≥25 kg/m 2 (the World Health Organization definition of overweight/obese) significantly increased RA risk by 15%, compared to BMI <25 kg/m 2 ; BMI ≥30 kg/m 2 (obesity) significantly increased RA risk by 21% to 31% compared to normal BMI [15-17]. Obesity may increase RA risk via systemic inflammation, as adipose tissue secretes pro-inflammatory adipokines [18].…”
Section: Introductionmentioning
confidence: 99%